Progress and paradox for women in US higher education. Issue 4 (3rd April 2017) - Smith, Daryl G.
Abstract : Gender, and especially the status of women, is certainly one of the most salient identities in all corners of the world. For some countries, the issues begin with the right to education at even the earliest ages. In the United States, there is a prevailing assumption, because women are a majority of the undergraduate and graduate populations in higher education that a threshold concerning access and equity has been reached. The story of gender, however, is a more complex one. This article will focus on the parallel notions of significant progress in some domains for women in higher education and the paradox that depending on the level, and depending on which women, progress and in some cases lack of progress is clear. The article will review changes over the last decades and address the deeper issues of institutional transformation and the emerging issues for policy including conceptualizations of gender.